2019
DOI: 10.1002/cam4.2586
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: lncRNA ABHD11‐AS1, regulated by the EGFR pathway, contributes to the ovarian cancer tumorigenesis by epigenetically suppressing TIMP2

Abstract: ObjectiveEpithelial ovarian cancer (EOC) is a common gynecologic malignancy characterized by extensive peritoneal metastasis and high mortality rate. ABHD11 Antisense RNA1 (ABHD11‐AS1) has recently been identified as a regulator of growth and metastasis in multiple tumors, including EOC. However, the biological function and potential mechanism of ABHD11‐AS1 in EOC remains poorly understood.MethodsImmunohistochemistry, western blot, and qRT‐PCR analysis were used to determine the expression pattern of ABHD11‐AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…17 Other than function as potential prognosis biomarkers for OC, lncRNAs have also been shown to be associated with the carcinogenesis and aggressive behavior of OC. 18 Here, in vitro functional assays revealed that overexpression of LEMD1-AS1 suppressed cell viability, proliferation, migration and invasion of OC cells. Moreover, in vivo subcutaneous xenotransplanted tumor model also indicated that overexpressed LEMD1-AS1 could suppress OC tumor growth, suggesting that LEMD1-AS1 might be a potential novel target for OC therapy.…”
Section: Discussionmentioning
confidence: 80%
“…17 Other than function as potential prognosis biomarkers for OC, lncRNAs have also been shown to be associated with the carcinogenesis and aggressive behavior of OC. 18 Here, in vitro functional assays revealed that overexpression of LEMD1-AS1 suppressed cell viability, proliferation, migration and invasion of OC cells. Moreover, in vivo subcutaneous xenotransplanted tumor model also indicated that overexpressed LEMD1-AS1 could suppress OC tumor growth, suggesting that LEMD1-AS1 might be a potential novel target for OC therapy.…”
Section: Discussionmentioning
confidence: 80%
“…This kind of regulation can be also in cis, although no examples have yet been described for OC. However, several examples have been described in OC for lncRNA-based PRC2 guidance, specifically of EZH2, an active subunit of PRC, to the loci of target genes: LINC00511 and TP73-AS1 guide EZH2 to the p21 locus [72,95]; LINC00702 guides it to the KLF2 locus [39]; LINC01210 to the KLF4 locus [27]; ABHD11-AS1 to the TIMP2 locus [136]; and UNC5B-AS1 to the NDRG2 locus [137].…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Thus, CREB1 activates HAS-AS2 transcription [79]; FOXO4 activates PVT1 transcription [74]; Nkx3-1, HNF-1, aMEF-2 and MEF-2A are TFs take part in the transcriptional regulation of LOC100190986 [21]. Some signaling pathways that trigger lncRNA transcription have also been identified; for instance, CXCL14 produced by surrounding fibroblasts triggers LINC00092 transcription [31]; TGF-β1 activates MALAT1 [21], PTAR [154] and PTAL [153] transcription; or pEGFR activates ABHD11-AS1 through STAT3 [136]. The lncRNA UCA1 has been described as being activated by a super-enhancer [157].…”
Section: Regulation Of Lncrna Expressionmentioning
confidence: 99%
“…The metalloproteinases degrade the extracellular matrix and facilitate metastasis initiation. Unsurprisingly, TIMP2 aberrant expression promotes cell growth and invasion in several malignancies [92].…”
Section: Lncrnas Involved In Epigenetic Mechanisms In Ovarian Cancermentioning
confidence: 99%
“…In this context, UNC5B-AS1 recruits EZH2 to inhibit NDRG2 transcription, promotes cell proliferation, and impairs apoptosis [ 91 ]. To confirm bioinformatic predictions, ABHD11-AS1 was experimentally proven to interact with EZH2 leading to the epigenetic repression of TIMP2 (TIMP metallopeptidase inhibitor 2) and further promoting invasion and metastasis [ 92 ]. This evidence sheds light on the function of ABHD11-AS1 in OC, albeit the inverse correlation between EZH2 and TIMP2 expression levels had already been detected in EOC tissues [ 99 ].…”
Section: Lncrnas Involved In Epigenetic Mechanisms In Ovarian Cancmentioning
confidence: 99%